Best Answer

3n + 2 + (3n + 3 - 3n + 1) =

3n + 2 + (3n + 3 - 3n + 1) =

3n + 2 + (4) =

3n + 6

Q: How do you get this 3n plus 2 plus (3n plus 3 - 3n plus 1)?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

n=1/3 or 0.333333333333333 repeated.

3n - 2n = n 3n - 2n = (3 - 2)n = 1n = n

Yes when multiplying. No when adding. 3n^3 + 3n^3 = 6n^3 3n^3 x 3n^3 = 9n^6

Un = n3 + n2 - 3n - 2 for n = 1, 2, 3, ...

Negative plus a negative is a negative. Ex. -1+-1=-2 Negative times a negative is a positive. -2*-2=4 But a negative [minus] plus a positive [plus] can be minus, zero or plus: For example, -3 + 2 = -1 -3 + 3 = 0 -3 + 4 = +1

Related questions

3n+2 + (3n+3 - 3n+1) = 3n+1+1 + (3n+1+2 - 3n+1) = 3*3n+1 + (9*3n+1 - 3n+1)= (3+9-1)*3n+1 = 11*3n+1.

If n is 2, then 3n plus 1 would equal 7.

3 + 3n = 9 + 2n + 4n n = -2

Simplify -6n+2+3n-3 So first let's combine the n terms. -6n and 3n is -3n since -6 and 3 is -3. Or, think of being in debt 6 dollars as -6n and someone gives you 3 dollars just because they are nice like those people who answer WikiAnswers.com. Now you are only in debt 3 dollars which we denote as -3 and n could be dollars or cents. Bottom line, when you combine the n's it is -3n. Next combine the numbers or constant terms, 2-3 is the same as 2+ (-3) which is -1. So the answer is -3n-1 which can also be written as -(3n+1)

3n + 4 = 7(- 4 from both sides)3n = 3(divide both sides by 3)n = 1

for the sequence, 3n +1, where n = 1,2,3,4......n =1: 3*1 + 1 = 3 + 1 = 4n =2: 3*2 + 1 = 6 + 1 = 7n =3: 3*3 + 1 = 9 + 1 = 10n =4: 3*4 + 1 = 12 + 1 = 13

2 + 3n = 4subtract 2 from each side2 - 2 + 3n = 4 - 23n = 2divide both sides integers by 3(3/3)n = 2/3n = 2/3=========check in original equation2 + 3(2/3) = 42 + 6/3 = 42 + 2 = 44 = 4=======checks

The expression "3n plus 1" represents a mathematical equation where a number, 'n,' is multiplied by 3 and then 1 is added to the result. To find the value, you would substitute a specific number in place of 'n' and perform the calculation. For example, if 'n' was 2, the equation would be 3(2) + 1 = 7.

The Series has the formula 3n + 1/2(n - 1)(n - 2) = 3n + 1/2(n2 - 3n + 2) which simplifies to, 1/2(n2 +3n + 2)

It depends! What is the value of N? Example If n= 3, the answer would be 11 (3n= 3x3=9 the plus the 2) Example 2 If n=7, ten the answer would be 23 (3n= 3x7=21 plus the 2wouldbe 23) Hope this helps

(3n + 15) / 2

3(3n - 1)(n + 1)